2018
DOI: 10.1007/s12041-018-0942-8
|View full text |Cite
|
Sign up to set email alerts
|

A study on the genotype frequency of $$-158~\hbox {G}\gamma $$ - 158 G γ ( $$\hbox {C}{\rightarrow }\hbox {T}$$ C → T ) Xmn1 polymorphism in a sickle cell trait cohort from Siwa Oasis, Egypt

Abstract: Sickle cell haemoglobinopathy is a genetic disorder caused by the presence of haemoglobin S (HbS) including sickle cell disease (SCD) (sickle cell anemia, HbS/β -thalassaemia and HbSC disease) and sickle cell trait. In Siwa Oasis, most remote oasis town in Egypt, the prevalence rate of sickle cell haemoglobinopathy is approaching 20%. The 1 polymorphism was reported to increase the HbF level ameliorating the severity of the SCD. The present study aims mainly to investigate the genotype frequency of -158Gγ (C→T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The most frequent genotype with the Xmn1 polymorphism observed was homozygosity (CC) for the absence of the Xmnl site in both HU+ and HU- populations. The homozygous mutant (TT), similar to the findings from a recent study 29 was also not observed in our study, thus limiting our ability to draw any conclusions on the influence of this genotype on HbF.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The most frequent genotype with the Xmn1 polymorphism observed was homozygosity (CC) for the absence of the Xmnl site in both HU+ and HU- populations. The homozygous mutant (TT), similar to the findings from a recent study 29 was also not observed in our study, thus limiting our ability to draw any conclusions on the influence of this genotype on HbF.…”
Section: Discussionsupporting
confidence: 67%
“…The association between HbF levels and polymorphisms presented by SNPs in BCL11A gene and the Xmn1 gene has been demonstrated in different populations. 11 , 16 , 25–27 , 29–35 While HbF regulation is highly diversified and genetically controlled, reproducing association studies across different populations, particularly of diverse genetic backgrounds and environmental setting is likely to produce different observations in different studies. Interestingly, we observed a slightly reduced Hb level in the HU+ group and speculate that, this could be due to crenation and subsequent lysing of RBC’s since HU plays a role in RBC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Sickle cell anemia (SCA) is a particularly common genetic disorder in some parts of Saudi Arabia [ 2 , 8 ]. The polymorphism in the β chain of Hb S and patient prognosis can be predicted by combining the levels of Hb F with a determination of which Xmn1 ′5 to G γ is present [ 9 ]. High levels of the former can interact with the latter to reduce disease severity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are designated as Senegal, Benin, Bantu, Cameroon, and Arab-Indian haplotypes. The latter was discovered with the presence of Xmn1 ′5 to G γ in the Arabian Gulf region and India with fewer clinical symptoms as the Hb F is present in high levels in comparison with the haplotypes in Africa [ 8 , 9 ]. The Senegal and Arab-Indian haplotypes are positive in Xmn1 ′5 to G γ , having the same mutation (C--T) and also a high level of Hb F as well [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation